MECHANISMS FOR IMPROVING PROSECUTORIAL SUPERVISION OVER THE ENFORCEMENT OF LAWS IN THE FIELD OF PRESCHOOL EDUCATION - Amonova, Gulshanoy (Oriental Journal of History, Politics and Law, 2025)
The importance of prosecutorial supervision over the enforcement of laws in the field of preschool education was highlighted. The necessity of digitalizing activities to enhance efficiency in this sector was substantiated. A proposal was developed to introduce necessary additions and changes to the “Kindergarten” information system of the Ministry of Preschool and School Education and to integrate this system with the prosecutor’s office. The implementation of a “risk analysis and assessment” system for prosecutorial supervision in the preschool education sector was justified as a crucial factor for increasing its effectiveness; its advantages and disadvantages were studied, and its project draft was developed.